How do hospitality entrepreneurs use their social networks to access resources? Evidence from the lifecycle of small hospitality enterprises. (May 2019) - Teixeira, Rivanda Meira; Andreassi, Tales; Köseoglu, Mehmet Ali; Okumus, Fevzi
Highlights: This study elucidates the use of social networks by entrepreneurs to access resources. Data was collected via semi-structured interviews with entrepreneurs in Sergipe State. In the start-up stage, entrepreneurs accessed fewer resources utilizing only family and friends. In the consolidation stage, entrepreneurs relied more on their weak links and accessed them with greater frequency. The mobilization of social networks is dynamic; the needs of entrepreneurs to use them change throughout the process. Abstract: This study investigates entrepreneurs' use of social networks to access resources during the conception, start-up, and consolidation stages of small enterprises in the hospitality industry in Sergipe State, Brazil. This study analyzes four cases of small hotel ventures, employing cross-case analyses to identify the patterns, similarities, and differences between the cases. The study findings highlight that, in the start-up stage, entrepreneurs access fewer resources, utilizing only family and friends, primarily as moral support. In the consolidation stage, entrepreneurs rely more on their weak links, accessing them with greater frequency. Mobilizing social networks is a dynamic process, and how entrepreneurs use these networks changes throughout the business-creation process. This is one of the first studies on how entrepreneurs use their social networks, especially in a developing economy.